Evaluation of Functional Outcome of Elbows after Resection Arthroplasty of Failed Total Elbow Replacement - Pal, Ananda Kisor (Indian J Orthop, 2019)
BACKGROUND: Recovery of elbow function is a challenging problem following resection arthroplasty after failure of total elbow prosthesis. The objective of this study is to evaluate long term functional outcome in a series of such patients. MATERIALS AND METHODS: Nineteen patients with twenty elbows who had failed total elbow arthroplasty (TEA) following the use of Baksi total elbow prosthesis needed removal of prosthesis during the period from 1978 to 2003. As two patients were lost to followup, 17 patients with 18 elbows (bilateral in one) were included in this study with a mean age of 44.3 years. Nine cases had uncontrolled infection, seven cases of aseptic loosening including one occurred after TEA for bilateral postburns ankylosis, and two had broken humeral stems. After removal of the prosthesis and its adjacent surrounding bone cement, the cut ends of humerus and ulna were approximated with number 5 Ethibond suture. Postoperatively, the elbow was immobilized in a plaster slab in 110° elbow flexion for 6 weeks followed by physiotherapy. The patients were evaluated for 15–19.4 (mean 16.3) years where functional results were compared at 10 years and 15 years following resection arthroplasty. RESULTS: The resected elbow initially remained flail but gradually regained stability, especially in the sagittal plane. Both the groups showed overall improvement from preoperative Mayo Elbow Performance Score (MEPS) 26.5 to postoperative mean MEPS at 10 years (69.6) and at 15 years (70) (P = 0.001). Postoperative mean DASH score was 36.62 at 10 years’ and 36.38 at 15 years’ followup, suggesting persistence of function of resected elbow in the passage of time. The results were good in 9 (50%), fair in 7 (38.8%), and poor in 2 (11.1%) patients. None had recurrence of infection. Transient ulnar nerve palsy was seen in three patients. Postoperatively, power of Biceps recovered up to Medical Research Council grade 4 and Triceps 2–3. CONCLUSION: Resection arthroplasty of elbow provided acceptable functional recovery in our series of patients with failed elbow prosthesis.